2013
DOI: 10.1111/jgs.12249
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum 25‐Hydroxyvitamin D Concentration and Optic Chiasm Volume

Abstract: In particular, low serum 25-hydroxyvitamin D (25OHD) concentrations are associated with poor visual acuity in older adults. 2 This association has been tentatively explained by the onset of age-related macular degeneration (AMD) in the case of hypovitaminosis D, 3,4 but no causal relationship has been established, 3,4 and other hypotheses have not been tested. For instance, because vitamin D is involved in neurophysiology and neuroprotection, 5-7 it was hypothesized that low 25OHD concentrations could result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
(16 reference statements)
2
12
0
Order By: Relevance
“…These findings are consistent with the growing epidemiological evidence on the deleterious effect of vitamin D insufficiency on eye health and function [6,7,13,14]. While previous research was primarily focused on macular conditions such as AMD [15,16], only one clinical study focused specifically on the association between vitamin D and POAG [17].…”
Section: Discussionsupporting
confidence: 84%
“…These findings are consistent with the growing epidemiological evidence on the deleterious effect of vitamin D insufficiency on eye health and function [6,7,13,14]. While previous research was primarily focused on macular conditions such as AMD [15,16], only one clinical study focused specifically on the association between vitamin D and POAG [17].…”
Section: Discussionsupporting
confidence: 84%
“…Since the calcarine sulcus is part of the primary visual cortex, which is essential for the conscious treatment of visual stimuli, our result is in agreement with previous epidemiological findings that hypovitaminosis D is associated with reduced visual performance among older adults . This association was tentatively explained by the onset of age‐related macular degeneration (AMD), glaucoma, or optic neuropathy in the case of hypovitaminosis D. However, no causal relationship has been established thus far, and the result of the present study suggests a novel mechanism possibly explaining how vitamin D influences vision, by an effect on the primary visual cortex trophicity rather than on the eye.…”
Section: Discussionsupporting
confidence: 92%
“…Annwelier et al found that the serum 25(OH)D levels were associated with optic chiasm volume [42], and in a vitro experiment, vitamin D was found to inhibit neovascularization in retinal tissue in a model of ischemic retinopathy [13]. What is more, proof of the VDR polymorphisms related with diabetic retinopathy was found.…”
Section: Discussionmentioning
confidence: 99%